2015
DOI: 10.1007/s12031-015-0536-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Brain Histamine and Serotonin, Norepinephrine, and Dopamine Systems: In Vivo Microdialysis and Electrophysiology Study

Abstract: Brain monoamines (serotonin, norepinephrine, dopamine, and histamine) play an important role in emotions, cognition, and pathophysiology and treatment of mental disorders. The interactions between serotonin, norepinephrine, and dopamine were studied in numerous works; however, histamine system received less attention. The aim of this study was to investigate the interactions between histamine and other monoamines, using in vivo microdialysis and electrophysiology. It was found that the inverse agonist of hista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Similarly, the role of the cholinergic system dysfunction as a possible pathophysiological mechanism in apathy has been suggested, notably by some pharmacological studies having demonstrated an improvement of apathy following anticholinesterasic drug intake (Devos et al, 2014). Moreover, and not surprisingly, several anatomical, biochemical and electrophysiological studies also point toward interactions between different neurotransmitters in the behavioural control (Flik et al, 2015;De Deurwaerdère and Giovanni, 2016). Further exploration of the respective roles of these other neurotransmission systems in the emergence of Parkinson's disease neuropsychiatric signs, and their potential interactions with the serotonergic and dopaminergic alterations, will be of major interest.…”
Section: Dopamine Serotonin and Non-motor Manifestations In Early Pamentioning
confidence: 87%
“…Similarly, the role of the cholinergic system dysfunction as a possible pathophysiological mechanism in apathy has been suggested, notably by some pharmacological studies having demonstrated an improvement of apathy following anticholinesterasic drug intake (Devos et al, 2014). Moreover, and not surprisingly, several anatomical, biochemical and electrophysiological studies also point toward interactions between different neurotransmitters in the behavioural control (Flik et al, 2015;De Deurwaerdère and Giovanni, 2016). Further exploration of the respective roles of these other neurotransmission systems in the emergence of Parkinson's disease neuropsychiatric signs, and their potential interactions with the serotonergic and dopaminergic alterations, will be of major interest.…”
Section: Dopamine Serotonin and Non-motor Manifestations In Early Pamentioning
confidence: 87%
“…Association of the serotonergic and dopaminergic systems also occurs in the activation of 5-HT 1B receptors leading to increase of dopamine release in the brain (Gonzalez-Burgos and Feria-Velasco, 2008), while neonatal lesions of raphe nuclei cause compensatory increase in number of dopaminergic fibers in adult rats (Bolte Taylor et al, 1998). Association of histaminergic system with other monoaminergic systems has been shown, for example H 3 R antagonists stimulate 5-HT, noradrenergic and dopaminergic neurotransmission (Flik et al, 2015). Trillo et al (2013) elaborated that monoaminergic systems are especially vulnerable in AD due to: 1) the fact that the number of monoaminergic neurons is low in the brain, 2) having long, unmyelinated axons, monoaminergic neurons have increased vulnerability to abnormalities of anterograde or retrograde transport, and 3) monoaminergic fibers innervate many regions affected by amyloid and tau pathology.…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…Improved methods enable more sophisticated experimental design and analysis. The improvement in the separation and quantification of the monoamines and their metabolites (De Benedetto et al, 2014), with excellent temporal resolution (1min (Gu et al, 2015)), and combination with electrophysiology (Flik et al, 2015) has brought direct measurements of brain amines in disease models or in response to drugs into standard practice. In combination with behavioural studies, microdialysis is a very useful experimental tool for the characterization of new models, such as birds (Ihle et al, 2015), that will lead to better understanding of the influences of monoamines on behavior.…”
Section: Mao Inhibition Raises Brain Amine Levelsmentioning
confidence: 99%